Biological threats and environmental pollutants, a lethal mixture for Mediterranean cetaceans? - Lauriano G; Marsili L; Maltese S; Fossi MC; DI GUARDO, Giovanni (Journal of the Marine Biological Association of the United Kingdom, 2013)
The possible existence of any cause–effect relationships between the concentrations of organochlorines (OCs) and the presence of Morbillivirus and Toxoplasma gondii infections was investigated in both free-living and stranded specimens of Stenella coeruleoalba, Tursiops truncatus, Globicephala melas, Balaenoptera physalus and Physeter macrocephalus from the Mediterranean Sea. High blubber concentrations of polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethane (DDT) were recorded in free-ranging G. melas. Tissue concentrations of PCBs and DDT in stranded T. truncatus(367 lipid weight (l.w.) and 143.7 mg/kg l.w., respectively) and S. coeruleoalba (139.9 l.w.; 92.9 mg/kg l.w.) were beyondthe PCB threshold value for the appearance of adverse effects in marine mammals. Evidence of T. gondii infection was molecularlydetected in three S. coeruleoalba and six T. truncatus.[.]